Using Wikis for Collaborative Writing in the ELT Classroom - Jolanta Hudson (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2018)
This study examines the use of an educational wiki to develop the second language (L2) writing skills of English language students who are placed on a two-week online course to develop skills in English for work-related purposes. It discusses the use of wikis for learning L2, focusing on learning writing through collaborative tasks. The discussion analyses views and theories on the use of wikis for developing writing skills and the issues associated with the use of wikis for collaborative tasks. The research engages L2 students and a teacher in a task using Wikispaces, an educational type of wikis. The data is collected via a questionnaire, interviews and the teacher’s diary. The study suggests wikis might usefully assist students with their L2 writing and that students are likely to value the opportunity to work collaboratively on a writing task or certain type of task. However, not all students would be expected to feel comfortable with the wiki technology and its features. As wikis are still increasingly popular in language classrooms, a more in-depth study that would take a closer look at the usefulness of wikis for such classroom tasks might bring new insights and interesting results to the discussion on wikis in the English language classroom (ELT). It is suggested, therefore, that future research with a larger and more diverse audience and with a more specific focus might provide better information in this regard.